If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x = -8y + 72 Reorder the terms: 9x = 72 + -8y Solving 9x = 72 + -8y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '9'. x = 8 + -0.8888888889y Simplifying x = 8 + -0.8888888889y
| 3(7+x)=24 | | 7x+5=21 | | 3x^3-24x^2+36x=0 | | 11k-8k-3=9 | | -x+7=8 | | (2x+3)(x-5)=2(x^2-6x+5) | | 3t+8(2t-6)+2=14t | | Y^2+2y-120=0 | | y=2.6 | | 7k-8-2(k-12)=52 | | 10+x^2-7x=0 | | a^2=24-10a | | 1/2=12+18 | | 2x^3-44x^2+240x=0 | | 8x+9+3=6 | | -4x^2(3x-7)=0 | | r^2-11r=-18 | | 10=0.1x^2+4x | | (4+z)=-1 | | (x+3)=5 | | c(210)= | | (12n-4)/2=1-10n | | 9-c=13 | | 4m=-8 | | 3(x+1)+1=3x+4 | | 12r=132 | | 2(3x+5)=6x+11 | | g(-7)=3 | | 3n+4=5(n+2)-3n | | y^2+6y+12x-39=0 | | 6+0.5x=8+0.3x | | 4(c+5)= |